A Literature Review of Credit Ratings - Bhenu Artha; Ainun Hertikasari (Journal of Business and Management Review, 2022)
The behavioural finance literature focuses on the impact of investor sentiment on the underlying value of individual stocks. Credit ratings can be viewed as a link between borrowers and issuers that reduce information asymmetry in the financial system through an independent view of creditworthiness. The purpose of this study was to determine the variables related to credit ratings. This research is a literature study, which uses 21 articles as study material. The results of this study indicate the variables related to credit ratings, both influencing and being influenced. This study did not find credit ratings used as a moderating variable, which can be used as research material in the future.